WHY FINANCIAL INDEPENDENCE IS CRUCIAL FOR WOMEN - Norboyeva Zuhraxon Alijon qizi (TADQIQOTLAR, 2025)
Abstract: This article looks at how women’s financial independence has changed throughout time, what obstacles they face now, and how financial autonomy affects women’s well-being. The government’s efforts to close the gender wage gap and encourage women’s economic involvement are highlighted by case studies from Australia, New Zealand, and Uzbekistan. Cultural traditions, pay disparity, and restricted access to financial resources continue to impede women’s financial independence despite continuous attempts. For women to have equal access to economic possibilities, the essay highlights the necessity of workplace diversity, financial education, and regulatory changes. Achieving financial independence advances social and economic advancement in addition to being crucial for gender equality.